Synthesis of CIGS absorber layers via a paste coating - Park, Jong Won; Choi, Young Woo; Lee, Eunjoo; Joo, Oh Shim; Yoon, Sungho; Min, Byoung Koun (ELSEVIER SCIENCE BV, 2009)
CuInxGa1-xSe2 (CIGS) thin films were prepared by a paste coating with the aim of developing a simpler and the lower cost method for fabricating the absorber layers of thin film solar cells. In particular, a paste of a Cu, In, Ga, and Se precursor mixture was first prepared, followed by a reaction between them at elevated temperatures after depositing the paste onto a glass substrate. No apparent change in composition was observed during thermal annealing at 450 degrees C in the absence of a gas-phase selenium source. A pre-annealing process at 250 degrees C under ambient conditions performed before annealing (450 degrees C) under reduction conditions reduced the level of carbon deposition in/on the films without perturbing the stoichiometry of the CIGS thin films. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: SOLAR-CELLS; CU(IN,GA)SE-2 NANOPARTICLES; SELENIZATION; PRECURSORS